A Regression Analysis on the Macroeconomic Variables Affecting Taiwan’s Export Value to the US before and after 2008 Financial Crisis - Tsai, Fong-Wen; Bernard, Prosper; Plaisent, Michel; Lin, Edward (Journal of Comparative International Management)

(untitled) (Management Futures, 2014)
The booming of international trade since 1980 has resulted in the sharp economic growth of Taiwan. It is therefore important to understand the influential factors and their impacts on Taiwan’s international trade and export. This research adopts multiple regression method to identify the respective influential macroeconomic variables affecting the export values of Taiwan to the U.S. before and after 2008 financial crisis. It also analyzes the correlations among these macroeconomic variables. The results of this research indicate that, the first lag period of: (1) Taiwan industrial production index, (2) exchange rate of U.S. dollar to New Taiwan dollar, (3) US Interbank real call loan rate, and (4) U.S. industrial production index are influential macroeconomic variables affecting export values of Taiwan to the U.S. before 2008 financial crisis. After 2008 financial crisis, the influential macroeconomic factors are the first lag period of (1) exchange rate of U.S. dollar to New Taiwan dollar, (2) Taiwan’s industrial production index, (3) Mainland China’s consumer price index yearly increment, and (4) Taiwan’swholesale price index yearly increment (excluding service).